The intelligent investor the definitive book on value investing - Graham, Benjamin (New York HarperBusiness Essentials, 2003)
The greatest investment advisor of the twentieth century, Benjamin Graham, taught and inspired people worldwide. Graham's philosophy of "value investing"?which shields investors from substantial error and teaches them to develop long-term strategies?has made The Intelligent Investor the stock market bible ever since its original publication in 1949.
Includes bibliographical references and index.
Keywords: Securities